BREEDING ECOLOGY OF NIGHT HERON (Nycticorax nycticorax Linne,1758) IN THE LAKE VAN BASIN, TURKEY - A. Durmuş; O. Adizel (Journal of Animal and Plant Sciences, 2010)
A study on breeding ecology of night heron (Nycticorax nycticorax) was conducted in the Lake Van Basin between 16 February 2006 and 04 October 2007 on four big islands inside the lake and sorrounding wetlands.The night heron only breeds on islands inside the lake in this region because it finds food in wetlands. Trees which numbers had been given previously were observed and, starting from pre-breeding period into March and June, data on nests and breeding were taken. The breeding period was about seven months (March – September). During this period, it was frequently observed that nests from the previous year were repaired and re-used. Both the male and the female repair the nest.Average dimensions of eggs laid on nests were measured as 49.33±3.2 mm in length, 32.19±1.35 in width, and with a weight of 29.66±5.01 grams. The number of eggs laid ranged from 1 to 6 per nest. In 1364 active nests observed within the entire breeding region, 4206 (92 %) of 4576 eggs hatched and 3923 (93 %) of all chicks managed to leave the nest. Brooding periods in 50 nests were observed separately in each breeding season. In 2006, average brooding period during the first period was 25.62±2.03 and it was 26.22±1.18 during the second period; in 2007, average brooding period during the first period was 26.10±1.69 and it was 25.60±1.76 during the second period. Juvenile growth periods for N. nycticorax have been observed as follows: in 2006, average 39.98±2.47 days during the first breeding period and 32.68±1.25 days during the second breeding period; in 2007, average 42.18±2.60 days during the first breeding period and 34.64±1.15 days during the second breeding period. A significant statistical difference has been observed between years and even periods in question (P < 0.01).
Keywords: Nycticorax nycticorax; The Night Heron; Ecology; Birds; Breeding; Lake Van; Turkey